1931
DOI: 10.1002/andp.19314000502
|View full text |Cite
|
Sign up to set email alerts
|

Elektronenbeugung und Molekülbau. (

Abstract: E l e k t r o m n n b e u y g umd MoZetciiZbnu Von R. W i e r l (Mit 30 Figuren)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1937
1937
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This is confirmed by electron diffraction measurements (Brockway 1936;Wierl 1931), and by the infra-red (Cassie 1935) and Raman (Anderson and others 1936) spectra. Boron tribromide (Anderson and others 1936) has a similar configuration.…”
Section: Assignmentsmentioning
confidence: 61%
“…This is confirmed by electron diffraction measurements (Brockway 1936;Wierl 1931), and by the infra-red (Cassie 1935) and Raman (Anderson and others 1936) spectra. Boron tribromide (Anderson and others 1936) has a similar configuration.…”
Section: Assignmentsmentioning
confidence: 61%
“…This has been confirmed by electron diffraction experiments (2) and, for condensed aromatic molecules, by X-ray analysis (3). Indeed, X-ray methods had shown that many substituted derivatives of benzene (including hexamethylbenzene, durene, benzoquinone, anthracene, naphthalene, chrysene, etc.)…”
Section: Non-planar Aromatic Moleculesmentioning
confidence: 88%
“…Its history at Caltech is a rather short one, however: after the structures of a few, mostly lead, compounds were measured with it, and a few less conventional ones (NpF 6 and PuF 6 ), it was effectively retired. 7 The COT problem 7 The reason: Verner resigned from Caltech to assume a position at the Union Carbide Research Institute. The apparatus was later "loaned" to Professor Lothar Schäfer at the University of Arkansas.…”
Section: The Postfellowship Yearsmentioning
confidence: 99%
“…Further details are found in the article cited [6]. The beauty of this system was that the cards could be used either for the calculation of radial distribution curves according to rD(r) = I (q) sin(qr) ( 1 ) or theoretical intensity curves according to the modified Wierl equation [7] …”
Section: Solving the Structure With Visual Datamentioning
confidence: 99%